The requirements and consequences of sections 17 (5) and 23 (5) of the Matrimonial Property Act 88 of 1984: a comparative scrutiny for the South African legal system - Seidel, Thorsten (Department of Private Law, 2023)
This thesis is a comparative scrutiny of sections 17 (5) and 23 (5) of the Matrimonial Property Act 88 of 1984. The comparison centres on the legal situation in South Africa, Germany and Switzerland. References, however, will also be made to other countries such as England, Scotland, France, Belgium, Spain, Sweden, Austria and Poland. Sections 17 (5) and 23 (5) of the Matrimonial Property Act 88 of 1984 provide that for legal transactions in respect of household necessaries both spouses are, respectively, jointly and severally liable [section 23 (5)] or may be sued jointly and severally [section 17 (5)]. As regards the question of liability for the debts arising from transactions in respect of household necessaries, the statutory provisions are relatively clear. However these statutory provisions give rise to many important questions other than the issue of liability such as the historical background, the ratio legis and the legal nature of sections 17 (5) and 23 (5) of the Matrimonial Property Act 88 of 1984, the requirements and the effects of sections 17 (5) and 23 (5) in respect of the contractual position of the spouses and the acquisition of ownership. Furthermore the question arises as to how the effects of sections 17 (5) and 23 (5) of the Matrimonial Property Act 88 of 1984 can be excluded. Unfortunately it would appear that the South African authorities have not yet grappled with many of these questions, in spite of the importance thereof. The author therefore attempts to submit his own answers. Furthermore the legal situation in Germany and Switzerland is presented. No attempt is made to answer questions which arise in these countries, since the primary object of the present thesis is the legal situation in South Africa. The author thus merely describes the legal situation in Germany and Switzerland and concentrates on the majority opinion in these countries. Only where, from the South African point of view it appears to be necessary, a short criticism is submitted. Finally the author compares the different legal systems, highlights weaknesses of the South African law and the advantages of the Swiss and German law in order to submit a proposal which could improve the current legal situation in South Africa.